Pemberhentian Ketua Dewan Perwakilan Rakyat Daerah Kabupaten/Kota dalam Masa Jabatannya - Fauzatil Azmi, Bona; Khairani, Khairani; Setiawan, Dian Bakti (Universitas Ekasakti, 2023)
The leadership of the Regional People's Representative Council (DPRD) can be dismissed at any time before their term of office ends, as happened in Solok Regency, Bukittinggi City and West Pasaman Regency. The three DPRD Chairmen were dismissed from their positions before the end of their terms of office. The problem in this research is what are the arrangements and procedures for dismissing the chairman of the district/city Regional People's Representative Council according to the relevant laws and regulations and whether the dismissal of the Chairman of the Regional People's Representative Council is in accordance with the governing regulations. This research aims to determine the arrangements for dismissing the chairman of the district/city DPRD according to relevant laws and regulations during his term of office according to regional government regulations, the mechanism for dismissing the Chair of the DPRD and the legal consequences of dismissing the Chair of the DPRD during his term of office on the implementation of the functions and duties of the DPRD in accordance with the problem formulation and the planned research objectives, the method used in this research is empirical juridical. The research results show that: there are two types of procedures for dismissing the chairman of the district/city Regional People's Representative Council, namely, through a proposal from a political party or through a complaint to the Honorary Board of the district/city Regional People's Representative Council. Research carried out in three regions, can be concluded that first the dismissal of the chairman of the district DPRD. Solok could not be carried out because there was not enough evidence of violating the code of ethics, while the dismissal of the Chairman of the Bukittinggi City DPRD could not be carried out after the Padang PTUN decision which stated that Parizal Hafni as Chairman of the Bukittinggi City DPRD won his lawsuit against DPP Gerindra and finally the dismissal of the Chairman of the District DPRD. West Pasaman can be implemented because it is in accordance with existing procedures/mechanisms.